A combined numerical and experimental investigation of minimum quantity lubrication applied to end milling of Ti6Al4V alloy. Issue 2 (15th September 2020) - Narayanan, Sabarish V.; Benjamin D., Mark; M. V., Hariharan; Keshav, Raja; Raj, D. Samuel
Abstract: Minimum Quantity Lubrication (MQL) has increased in popularity over the last two decades, owing to its economic and environmental benefits over flood cooling. But there are still challenges in the form of mist formation, an inability to carry away chips, and contradicting results in terms of surface roughness and tool wear. This study is a combined experimental and computational investigation to compare the effects of flood lubrication and MQL on the milling of a common low-machinability aerospace-grade titanium alloy. The influence of process parameters viz. feed, speed and depth of cut on the cutting forces, machining zone temperature and surface finish is studied. The cutting forces reduced by up to 35% and temperatures reduced by up to 47% as compared to flood lubrication across the different parameter range tested. Surface roughness in MQL was about 35% lower than that produced in flood lubrication. Computational fluid dynamics analysis is then carried out to compare the temperature profile and heat transfer to the cutting tool and the analysis proves that MQL offers better thermal gradient than flood cooling (∼30 times higher than MQL) thereby giving rise to lower cutting forces and consequently increased tool life.